Learning Styles According to The VARK Model for Eighth Grade Students in Biology - Kani Omer Ismael; Waad Mohammed Najat Sabri (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research aimed to know the learning styles according to the (VARK) model of the eighth-grade students in the subject of biology. The researchers used the descriptive method that was appropriate with the nature of the research. And the research community included eight-grade students in basic schools at the Central Education Directorate in Erbil, the number of research community is (15389) students, (7128) male and (8261) female, the sample members is (690) students from (408) schools for the academic year 2021-2022. In order to reach its goal, the researchers used Fleming (16) item questionnaire scale after making sure of its validity and reliability (0.88), the researchers applied it to the research sample consisting of (3) schools (Betwata basic school), (Dldar basic school) and (Hezha basic school), researchers have started the procedural from 10-2-2022 to 22-2-2022. After collecting and analyzing information through statistical programs (SPSS), the researchers reached these results: the best learning patterns for eighth grade students is visual in favor of male; the best learning patterns for eighth grade students is kinesthetic in favor of female. In the end, researchers presented some recommendation for teachers and educators about learning styles, and patterns in addition to suggesting some titles of research that necessary doing them in the future by other researchers.